MUTU ORGANOLEPTIK DAN KADAR INDEKS GLIKEMIK PADA PEMBUATAN PUDING UBI UNGU (IPOMOEA BATATAS) DENGAN PENAMBAHAN KURMA (PHOENIX DACTYLIFERA) SEBAGAI ALTERNATIF SNACK PENDERITA DIABETES MELITUS - Zulhira, Puja; Nurhamidah, Nurhamidah; Nova, Maria (Ensiklopedia of Journal, 2025)
The prevalence of diabetes mellitus in West Sumatra is 1.8% of the 3.7 million population over the age of 15 years (Ministry of Health of the Republic of Indonesia 2020). Purple sweet potatoes are high in fiber which is useful for stabilizing blood sugar and cholesterol. Dates can be a good source of nutrition for healthy individuals and patients with Diabetes Mellitus.This study aims to determine the organoleptic quality and glycemic index levels in the manufacture of purple sweet potato pudding with the addition of dates as an alternative snack for Diabetic Mellitus patients. This type of research is an experimental study, using a Complete Randomized Design (RAL) with 1 control of 3 treatments and 2 replicates. This research was conducted in February - August 2024 with subjective observation of taste (organoleptic test) with 25 moderately trained panelists. Nutrient analysis was carried out in the Eka Sakti University Laboratory. Objective observation through the analysis of the glycemic index rate in pudding. The result of the study was that the most preferred color of the panelists was the P1 treatment, which was 72% with purple. The most preferred aroma is the P0 and P3 treatments, which is 60% with a fragrant aroma, the most preferred texture is the P0 treatment, which is 80% with a soft texture. The most preferred taste is P1 and P3 treatment, which is 68% with sweetness. . The glycemic index value obtained from purple sweet potato pudding was 96.6. It is recommended that the public can take advantage of purple sweet potatoes that can be processed into pudding and many other innovations made from purple sweet potatoes It is not recommended for people with diabetes mellitus to consume purple sweet potato pudding with the addition of dates because it has a high glycemic index level.Keywords : Pudding, Purple Sweet Potato, Dates, Glycemic Index, Diabetes Mellitus